PENGARUH BEBERAPA SPESIES FUNGI MIKORIZA ARBUSKULAR PADA MEDIA TANAH DENGAN pH BERBEDA TERHADAP PERTUMBUHAN SEMAI KEMIRI (Aleurites moluccana (L.) Willd.) - Ristiyanti, Ristiyanti; Yusran, Yusran; Rahmawati, Rahmawati (Universitas Tadulako, 2014)
The research aim was to determine the effect of some species AMF in the soil with different pH on the growth of Kemiri (Acacia mangium Willd.) seedlings. This research was conducted in the nursery of Dinas Kehutanan Provinsi Central Sulawesi from April to June 2014. Soil analysis was carried out in the Laboratory of Soil Science, Agriculture Faculty, Tadulako University. The experiment was laid out in a Randomized Complete Design (RCD) Faktorial, treatments AMF species with four levels, i.e. without FMA (M0), Glomus etunicatum (M1), Glomus deserticola (M2) dan Gigaspora margarita (M3). Soil pH (H2O) two levels i.e. pH 5.05 (P1) and pH 6.07 (P2), so there are eight treatment combinations. The results showed that the treatment species of Gigaspora margarita (M3) gave the highest response to the increase in height increment (24.3 cm), shoot fresh weight (19.9 gr), dry weight of shoots (5.41 gr) and root dry weight (0.485 gr) of A. Mangium seedlings, while Glomus etunicatum species (M1) gave the highest response in root fresh weight (1,445 gr). Further, the higher shoot dry weight (4.6275 gr) was achieved by soil pH 6.2 (P2). Combination treatment of Gigaspora margarita and soil pH 6.07 (M3P2) had significant effect only on the shoot dry weight. But in general, the combination treatment of Gigaspora margarita and soil pH 5.05 (M3P1) gave the highest response to the increase in height increment (24.4 cm), shoot fresh weight (19.95 grams), root fresh weight (1.6 grams) and root dry weight (0.503 grams). All treatment combinations were produce seedling quality index (SQI) that all was feasible planted, where the highest SQI (0.28) was achieved by combination treatment between Gigaspora margarita and soil pH 5.05 (M3P1). Keywords: Arbuscular Mycorrhizal Fungi, Soil pH, Aleurites moluccana (L.) Willd